Women's Strategic Role In Enhancing Growth, Innovation, And Sustainability Of The Halal Economy In The Modern Era - Azahra Putri Afifah; Qeis Hafidz Nurhamsah; Sumarta; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This research examines the strategic role of women within Indonesia’s halal economy, focusing on their contributions, structural challenges, and developmental opportunities in the digital era. Women have proven to be key actors in strengthening halal MSMEs (Micro, Small, and Medium Enterprises), particularly in the food, Muslim fashion, and cosmetics sectors, contributing significantly to family economic resilience and national economic growth. Using a qualitative-descriptive approach based on secondary data analysis, this study explores the dynamics of women’s contributions within the halal value chain as well as the obstacles they face. These include limited access to Sharia financing, uneven digital literacy, the complexity of halal certification, and socio-cultural barriers that restrict women’s participation in productive economic activities. The thematic analysis indicates that digitalization opens vast opportunities for women to expand their market reach through e-commerce and Sharia-based marketplaces, while the global trend of the halal lifestyle offers expansion opportunities at the international level. This research also highlights the importance of government policy support through the simplification of halal certification, improved access to Sharia financing, and community-based empowerment programs. Theoretically, these findings affirm that women act not only as economic players but also as moral agents who maintain the integrity of Sharia values in production and marketing. The implications of this research emphasize the urgency of multi-stakeholder synergy to create a halal ecosystem that is inclusive, responsive, and sustainable. Consequently, women's empowerment is a strategic element in strengthening the competitiveness of the national halal industry and achieving sustainable economic development based on Sharia values.